2014
DOI: 10.1007/s40520-014-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

The identification of fall history using maximal and rapid isometric torque characteristics of the hip extensors in healthy, recreationally active elderly females: a preliminary investigation

Abstract: Early rapid strength production of the hip extensor muscles may be a sensitive and effective measure for discriminating between elderly females of different fall histories. These findings may provide important insight regarding implications for the assessment of fall risk and in the development of proper training programs aimed at minimizing the occurrence of falls and other balance-related injuries in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The greater exercise-induced depression of force capacities for the eccentric actions across a 30-min recovery period shown in the present study is suggestive of a relatively extended period of time whereby physical activities may be compromised in terms of both optimal performance as well as potential for injury as a result of low eccentric force production abilities. This finding appears to be particularly useful in the context of this study for the reason that these depressed strength responses were demonstrated for the eccentric actions specifically for the hamstrings muscles, which is a key contributing muscle group toward injury risk profiling (specifically to the functional eccentric hamstrings to concentric quadriceps ratio) (Jenkins et al 2013), as well as being a sensitive muscle group for identifying/ discriminating both athletic (Jenkins et al 2013;Thompson et al 2013) and clinical-based functional status (Bento et al 2010;Palmer et al 2014).…”
Section: Discussionmentioning
confidence: 85%
“…The greater exercise-induced depression of force capacities for the eccentric actions across a 30-min recovery period shown in the present study is suggestive of a relatively extended period of time whereby physical activities may be compromised in terms of both optimal performance as well as potential for injury as a result of low eccentric force production abilities. This finding appears to be particularly useful in the context of this study for the reason that these depressed strength responses were demonstrated for the eccentric actions specifically for the hamstrings muscles, which is a key contributing muscle group toward injury risk profiling (specifically to the functional eccentric hamstrings to concentric quadriceps ratio) (Jenkins et al 2013), as well as being a sensitive muscle group for identifying/ discriminating both athletic (Jenkins et al 2013;Thompson et al 2013) and clinical-based functional status (Bento et al 2010;Palmer et al 2014).…”
Section: Discussionmentioning
confidence: 85%
“…RTD (Nm·s −1 ) was calculated from the linear slope of the torque – time curve at 0–50 ms (RTD50), similar to the procedures of previous studies [29,30]. This time interval was selected because it has been previously shown that the RTD within the first 50 ms may provide unique physiological information when compared to PT [8,30] or RTD at 200 ms [31,32]. The onset of contraction was determined as the point when the torque signal reached 4 Nm [29].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the purpose of the present study was to examine the relationships between maximal and rapid strength and functional balance performance in career firefighters. Based upon previous literature 9 11 , 20 , we hypothesized that leg flexion rapid strength at early time intervals (i.e. 50 ms) would be the variable most strongly associated with functional balance performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the time needed to react and prevent a fall is shorter than the time required to reach maximal strength; therefore, the ability to generate force/torque rapidly may be critical in preventing STF-related injuries 10 12 . Furthermore, rapid torque production at early (i.e., 50 ms), but not late (i.e., 200 ms), time intervals have been suggested to be a better predictor of falls in the elderly 11 . However, these observations may also be muscle group specific as previous authors 10 have demonstrated that the leg flexors are more predictive of previous falls history than the leg extensors.…”
Section: Introductionmentioning
confidence: 99%